THE EFFECT OF LITIGATION RISK AND GOOD CORPORATE ON QUALITY OF FINANCIAL STATEMENTS IN BANKING COMPANIES IN INDONESIA STOCK EXCHANGE YEAR 2012-2016 - Rahma Purnami; Amir Hasan; M. Rasuli (PEKBIS, 2018)
The purpose of this study is to examine and analyze the effect of litigation risk,institutional ownership, managerial ownership, board of directors, independentcommissioners, and audit committee partially and simultaneously to the quality offinancial statements. The population of this study are all companies engaged inbanking that go public in Indonesia Stock Exchange in 2012 until the year 2016 asmany as 36 companies. Sampling using purposive sampling method. Samples thatmeet the criteria there are 31 companies, the method of data analysis using multiplelinear regression. Test results show that litigation risks, institutional ownership,independent commissioners, and audit committees have a significant influence onthe quality of financial statements. While managerial ownership and board ofdirectors have no significant effect to the quality of financial statements.Simultaneously the risk of litigation, institutional ownership, managerial ownership,board of directors, independent commissioner and audit committee affect the qualityof financial statements can be seen from F count (5.883)> F table (3.172).